Synthesis and Spectroscopic Studies of Some Heterocyclic Compounds (Oxazepane -4, 7-Dione, Azetidin-2-one) Derived from 2-Chloro -1, 8-Naphthyridine-3-Carbaldyhyd and Studying their Bacterial Activity - Khamaael M. Fayyadh (Journal of Global Pharma Technology, 2018)
Some new 2-chloro -1,8-Naphthyridine-3-carbaldyhyd  (K1) has been synthesized using N-acetyl-2-amino pyridine with through Vilsmeier-Haack cyclization to  preparation the compounds of Synthesis of  3-chloro-4-(2-chloro1,8-Naphthyridine-3-yl)-1-phenylenazetidin-2-one by ring closer reaction through the reaction of the compound (K5-7) with chloro acetyl chloride in presence of drops of tri ethyl amine in 1,4-dioxane ,andas has been prepared (R) 2-(2-chloro1,8-Naphthyridine-3-yl)-1-phenyl-1,3-oxazepane-4,7-dione from reaction the compound (K8-10) with  of Malic anhydride ,The newly synthesized compounds were characterized by spectroscopic evidences such as IR and 1H NMR. The synthesized compounds were screened for their in vitro antibacterial activity, compounds were shown good activity.Keywords: 1, 8-naphthyridine, Vilsmeier-Haack, Azetidine, Oxazepane-4, 7-Dione.